Territory as Patrimony: The Case of Puente Mulas in Belén, Costa Rica - Revelo Vallejo, Erika (2022)
This article determines the patrimonial elements present in Puente Mulas, a territory in Belén. Through the identification of the social and cultural values of its community, this research aims at contributing to the community’s efforts towards the protection and recovery of this territory. In order to gather community’s stories, semi-structured interviews and anecdote contests have been deployed. As a result, it is argued that Puente Mulas is a territory which is composed of an interacting array of elements, practices and particular shared symbols that constitute its population’s identity and well-being. It is pointed out that the most effective way for preserving and acknowledging Puente Mulas’s meaning for Belen’s residents is through a process of patrimonization that deeply includes the community.